2003
DOI: 10.3402/polar.v22i2.6451
|View full text |Cite
|
Sign up to set email alerts
|

Snow research in Svalbard—an overview

Abstract: This paper summarizes the most signifi cant snow-related research that has been conducted in Svalbard. Most of the research has been performed during the 1990s and includes investigations of snow distribution, snowmelt, snow pack characteristics, remote sensing of snow and biological studies where snow conditions play an important role. For example, studies have shown regional trends with about 50 % higher amounts of snow accumulation at the east coast of Spitsbergen compared to the west coast. Further, the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 37 publications
0
38
0
2
Order By: Relevance
“…The region's mean annual air temperature is −3.75°C (2000–2011) [ Christiansen et al , ], and the average total annual precipitation is 190 mm, of which about half falls as snow [ Førland et al , ]. The snow is largely redistributed by wind, as is typical for such valleys on Svalbard [ Winther et al , ], leading to an average snow depth of only around 20 to 30 cm. The maritime setting causes changeable winter conditions in Adventdalen with large temperature variations ranging from around −30°C to warm spells slightly above 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…The region's mean annual air temperature is −3.75°C (2000–2011) [ Christiansen et al , ], and the average total annual precipitation is 190 mm, of which about half falls as snow [ Førland et al , ]. The snow is largely redistributed by wind, as is typical for such valleys on Svalbard [ Winther et al , ], leading to an average snow depth of only around 20 to 30 cm. The maritime setting causes changeable winter conditions in Adventdalen with large temperature variations ranging from around −30°C to warm spells slightly above 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…The project was contin− ued on a greater number of glaciers in 1998-1999, generally supporting earlier re− sults . The most significant achievements in snow research on Svalbard were gathered and summarized by Winther et al (2003). An algorithm for estimation of winter accumulation on Spitsbergen glaciers on the basis of dis− tance to the open sea and basic meteorological data from coastal stations was pro− posed by Grabiec (2005).…”
Section: Introductionmentioning
confidence: 99%
“…1 over the solar spectrum. Current snow and sea-ice albedo parameterizations are highly simplistic, but over the last two decades, substantial knowledge of the reflective characteristics of snow, glaciers, and sea ice has been gained, and a wide variety of field measurements (Grenfell and Perovich 2004;Aoki et al 2003;Winther et al 2003;Gerland et al 1999;Perovich et al 2002;Oerlemans and Knap 1998;Perovich et al 1998;Betts and Ball 1997;Baker et al 1991;Winther et al 1999) and theoretical studies (Brock et al 2000;Gerland et al 2000;Roesch 2000;Sergent et al 1993;Winther 1993;Baker et al 1990,Marshall 1989Winther et al 2002) have been reported. Therefore, it seems timely to utilize this detailed knowledge to improve the parameterization of snow albedo in climate models.…”
Section: Introductionmentioning
confidence: 99%